Hubungan Faktor Risiko Ergonomi dan Keluhan Cumulative Trauma Disorders pada Dokter Gigi di PT. X Tahun 2014 - Winihastuti, Hany (UI Scholars Hub, 2016)
Dentist’s works have kind of risks related with Cumulative Trauma Disorders (CTDs). This research’s aim is to explain ergonomic factors and CTDs that happens to dentist. Cross sectional method is used in this research along with 44 dentis in hospitals and cliniques X as samples. The usage of RULA and MB Ruler in this research is supported the researcher to assess the work’s postures on the upper arm, forearm, wrist, neck, torso and leg.The study found that dentists who complained of CTDs as much as 72.7%. Bivariate analysis showed a relationship between the duration and the incidence of complaints CTDs (p = 0.045),and between exercise habits with the onset of complaints CTDs (p = 0.045). Exercising regularly, improving ergonomic working position can be done in order to prevent CTDs